PUERPERAL WOMEN'S PERCEPTIONS ABOUT EPISIOTOMY - Vanessa Aparecida Rezende Dengo; Rosana dos Santos Silva; Silvana Regina Rossi Kissula Souza; Juliane Dias Aldrighi; Marilene Loewen Wall; Franciane Zabloski Vieira Cancela (Universidade Federal do Paraná, 2016)
The objective of the present study was to know how parturient women were informed and guided regarding the undertaking of episiotomy during childbirth. A qualitative and descriptive study was conducted with eight puerperal women hospitalized in a rooming-in of a public maternity hospital in the state of Paraná. Data were collected in February 2015, by means of semi-structured interviews. The following topics emerged from the data analyzed based on thematic analysis: Episiotomy: the known unknown; "Cutting" the right of choice; Being unaware of the episiotomy's consequences. Women were not informed and guided regarding the episiotomy's procedure, which leads to a misunderstanding about this practice and the limitation of women's right of choice. This shows the need for increasing knowledge and rescuing women's autonomy during the childbirth and birth process.